Utilization of the Environment as a Source of Learning Physical Education in Junior High Schools in Martapura City - M.Rajib Ansyarullah; Arie Rakhman; Akhmad Amirudin (Universitas Negeri Semarang, 2025)
This study aims to describe the level of knowledge, utilization patterns, strategies, and obstacles of Physical Education teachers in utilizing the surrounding environment as a learning resource in junior high schools in Martapura City. The study used a quantitative method with a descriptive design, involving all Physical Education teachers in junior high schools in Martapura City totaling 12 teachers through a total sampling technique. The main research instrument was a questionnaire with a five-point Likert scale consisting of 13 questions regarding knowledge and frequency and 9 supporting questions regarding strategies and obstacles to environmental utilization. The results showed that the majority of Physical Education teachers had knowledge in the low category (42%), while the frequency of environmental utilization was dominated by the moderate category (50%). The combined tabulation of knowledge and frequency also showed that (42%) of teachers were in the moderate category. The most common utilization strategy was the use of school fields (70%), followed by the surrounding natural environment (27%), while public sports facilities and city parks were rarely utilized. The main obstacles faced included limited space, weather, student safety, distance, cost, and accessibility of facilities. The conclusion of this study shows that the use of the surrounding environment as a source of learning physical education in junior high schools in Martapura City is still not optimal, so it is necessary to increase training, mentoring, and development of facilities so that physical education learning becomes more innovative, effective, and contextual.